Neuroinflammation in retinitis pigmentosa: Therapies targeting the innate immune system - Zhao, Ling; Hou, Chen; Yan, Naihong (Frontiers in Immunology, 2022)
Retinitis pigmentosa (RP) is an important cause of irreversible blindness worldwide and lacks effective treatment strategies. Although mutations are the primary cause of RP, research over the past decades has shown that neuroinflammation is an important cause of RP progression. Due to the abnormal activation of immunity, continuous sterile inflammation results in neuron loss and structural destruction. Therapies targeting inflammation have shown their potential to attenuate photoreceptor degeneration in preclinical models. Regardless of variations in genetic background, inflammatory modulation is emerging as an important role in the treatment of RP. In this review, we summarize the therapeutic strategies targeting ocular inflammation in RP, focusing on the modulation of innate immune signals, including TNFα signaling, TLR signaling, NLRP3 inflammasome activation, chemokine signaling and JAK/STAT signaling. In addition, we describe epigenetic regulation, the gut microbiome and herbal agents as prospective treatment strategies for RP in recent advances.